Facile and scalable preparation of highly luminescent N, S co-doped graphene quantum dots and their application for parallel detection of multiple metal ions. Issue 32 (12th April 2017) - Shen, Chao; Ge, Shuyan; Pang, Youyou; Xi, Fengna; Liu, Jiyang; Dong, Xiaoping; Chen, Peng
Abstract : New and bright N, S co-doped GQDs are synthesized and serve as fluorescence probes for parallel and selective detection of Fe 3+, Cu 2+ and Ag + ions in biological and environmental samples. Abstract : Sensitive and selective detection of metal ions is important for environmental monitoring and biological studies because metal ions play crucial roles in many physiological and pathological processes including cellular metabolism, enzymatic activities, as well as DNA and RNA syntheses. In this work, new nitrogen and sulfur co-doped graphene quantum dots (N, S-GQDs) are synthesized and serve as fluorescence probes for parallel and specific detection of Fe 3+, Cu 2+ and Ag + ions. The N, S-GQDs are synthesized based on one-step bottom-up molecular fusion in a hydrothermal process with a high yield of 87.8% and possibility of mass production. The as-prepared N, S-GQDs exhibit a single-layer graphene structure, high crystallinity and uniform size (∼2.1 nm). Successful co-doping of N and S atoms in the lattice of GQDs not only enables bright blue fluorescence with high absolute photoluminescence quantum yield (23.2%) but also provides unique selectivity towards some metal ions. With the help of different masking agents, N, S-GQDs are able to differentially detect Fe 3+, Cu 2+ and Ag + ions in a mixture with low detection limits (8 nM, 250 nM and 50 nM, respectively). Moreover, detection of Fe 3+, Cu 2+ and Ag + in complex biological (serum) and environmental samples (river water) is demonstrated.